Mixtures of chemicals in pregnancy and their effects on cognitive and fine motor abilities in childhood - Brennan Kearns, Pavla; González, Llúcia; Soler-Blasco, Raquel; Andiarena, Ainara; Santa-Marina, Loreto; Casas, Maribel; Burgaleta, Miguel; Vrijheid, Martine; Guxens, Mònica (Environmental research, 2025)
This study evaluates effects of a mixture of 29 chemicals in pregnancy (organochlorine compounds, per – and polyfluoroalkyl substances, phenols, and phthalates) on cognitive abilities (working memory, attentional function, visuomotor attention, cognitive flexibility, verbal and non-verbal intelligence, information processing speed, risky decision making) and fine motor function in childhood. Data from over 2000 mothers and their children that take part in the INfancia y Medio Ambiente in Spain were analyzed. Quantile-based g-computation estimated joint effects of chemical mixtures on the outcomes, adjusting for confounders and using inverse probability weights to mitigate selection bias. The overall mixture of chemicals was linked to lower visuomotor attention (i.e., slower response time, +0.2 min, 95 % CI 0.0 to 0.4 for the second; +0.4 min, 95 % CI 0.0 to 0.8 for the third; and +0.7 min, 95 % CI 0.0 to 1.3 for the fourth quartile, relative to the first quartile). Counterintuitively, the overall mixture of chemicals was related to higher verbal intelligence (+1.5 points, 95 % CI 0.1 to 3.0 for the second; +3.0 points, 95 % CI 0.1 to 6.0 for the third; and +4.6 points, 95 % CI 0.2 to 9.0 for the fourth quartile, relative to the first quartile). However, neither of these associations survived multiple testing correction. Our study does not provide strong evidence that prenatal exposure to a mixture of organochlorine compounds, per – and polyfluoroalkyl substances, phenols, and phthalates affects cognitive abilities or fine motor function in childhood. •Prenatal exposure to 29 chemicals is not linked to most cognitive or motor functions.•Chemical mixture linked to lower visuomotor attention, higher verbal IQ, but not robust.•Findings do not support an effect of these chemicals on neurodevelopment.